Effect of soil chemical fertilization on the diversity and composition of the tomato endophytic diazotrophic community at different stages of growth - Collavino, Mónica M. (2020)
The aim of this work was to gain a more comprehensive and perspicacious view of the endophytic diazotrophic community (EDC) of tomato plant bacteria and assess the effects of chemical fertilization and the plant phenologic stage on the status of those microbes. When the EDC of stem and roots from tomato plants grown in a greenhouse with and without exogenous chemical fertilization was examined by pyrosequencing the nifH gene during the growth cycle, a high taxonomic and phylogenetic diversity was observed. The abundant taxa were related to ubiquitous endophytes such as Rhizobium or Burkholderia but also involved anaerobic members usually restricted to flooded plant tissues, such as Clostridium, Geobacter, and Desulfovibrio. The EDC composition appeared to be dynamic during the growth phase of the tomato, with the structure of the community at the early stages of growth displaying major differences from the late stages. Inorganic fertilization negatively affected the diversity and modified the profile of the predominant components of the EDC in the different growth stages. Populations such as Burkholderia and Geobacter plus the Cyanobacteria appeared particularly affected by fertilization.Our work demonstrates an extensive endophytic diazotrophic diversity, suggesting a high potential for nitrogen fixation. The effect of the phenologic stage and inorganic-chemical soil fertilization on the community structure indicated a dynamic community that responded to environmental changes. These findings contribute to a better understanding of endophytic associations that could be helpful in assisting to shape the endomicrobiome that provides essential benefits to crops.